Sarilumab monotherapy or in combination with non-methotrexate disease-modifying antirheumatic drugs in active rheumatoid arthritis: A Japan phase 3 trial (HARUKA). Issue 2 (3rd March 2020) - Kameda, Hideto; Wada, Kazuteru; Takahashi, Yoshinori; Hagino, Owen; van Hoogstraten, Hubert; Graham, Neil; Tanaka, Yoshiya
Abstract: Objectives: To determine long-term safety and efficacy of sarilumab as monotherapy or with non-methotrexate (MTX) conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) in Japanese patients with active rheumatoid arthritis (RA). Methods: In this double-blind, randomized study (NCT02373202), patients received subcutaneous sarilumab 150 mg q2w (S150) or 200 mg q2w (S200) as monotherapy or with non-MTX csDMARDs for 52 weeks. The primary endpoint was safety. Results: Sixty-one patients received monotherapy (S150, n  = 30; S200, n  = 31) and 30 received combination therapy (S150 + csDMARDs, n  = 15; S200 + csDMARDs, n  = 15). Rates of treatment-emergent adverse events (TEAEs) were 83.3%/90.3%/93.3%/86.7% for S150/S200/S150 + csDMARDs/S200 + csDMARDs, respectively. Nasopharyngitis and neutropenia were the most frequently reported TEAEs. One serious infection was reported in each monotherapy group and in the S200 + csDMARDs group. There were no cases of grade 4 neutropenia; no patients with grade 3 neutropenia experienced associated serious infection. Improvements in ACR20/50/70 response rates were generally similar between the two monotherapy groups and between the two combination groups; improvements in physical function (Health Assessment Questionnaire-Disability Index, HAQ-DI) and DAS28-CRP were observed at weeks 24 and 52 (all groups). Conclusion: The safety profile of sarilumab was consistent with known class effects of interleukin-6 signaling blockade therapeutics. Sarilumab as mono- or combination therapy improved clinical signs/symptoms and physical function in Japanese RA patients.